Забезпечення фінансово-економічної безпеки підприємництва : методичні рекомендації до проведення практичних занять із навчальної дисципліни для здобувачів вищої освіти першого (бакалаврського) рівня за спеціальністю D7 «Торгівля» денної та заочної форм навчання [Електронний ресурс] - Литовченко, Олена Юріївна; Lytovchenko, Olena (Харків : Харківський національний університет імені В. Н. Каразіна, 2026)
Методичні рекомендації спрямовані на підвищення ефективності засвоєння навчального матеріалу, розвиток аналітичного мислення, формування вмінь оцінювати загрози та ризики, приймати обґрунтовані управлінські рішення в умовах сучасного економічного середовища. спрямовані на закріплення теоретичних знань та формування практичних навичок у сфері забезпечення фінансово-економічної безпеки суб’єктів підприємницької діяльності.

The methodological recommendations are aimed at enhancing the effectiveness of learning the educational material, developing analytical thinking, and forming the ability to assess threats and risks, as well as to make well-founded managerial decisions in the context of the modern economic environment. They are intended to reinforce theoretical knowledge and develop practical skills in the field of ensuring the financial and economic security of business entities.This publication is intended for students of higher education in Specialty D7 – Trade, as well as for anyone interested in the issues of ensuring the financial and economic security of entrepreneurial activity.
Ensuring financial and economic security of entrepreneurship : methodological recommendations for conducting practical classes in the academic discipline for students of the first (bachelor's) level of higher education, specialty D7 "Trade" full-time and part-time forms of study [Electronic resource]
Електронне навчальне видання комбінованого використання. Можна використовувати в локальному та мережному режимі. В авторській редакції
Keywords: SOCIAL SCIENCES::Business and economics; SOCIAL SCIENCES::Social sciences::Education::Subject didactics; безпека; фінансово-економічна безпека; ризик; загроза; адаптація; економічна розвідка; security; financial and economic security; risk; threat; adaptation; economic intelligence